Feasibility of photovoltaic system in midi-lisy and panoramo equipment for pipeline rehabilitation - Pablo Ricardo Aguirre-Espinoza; Mario Guadalupe González-Pérez; Yefer Asprilla-Lara (Dyna, 2022)
Changes in the availability and accessibility of alternative energy sources have been observed in recent years. This study analyzes the economic viability of the use of photovoltaic solar energy systems in equipment for the control and inspection of drinking water pipes. For this, the consumption, costs and operating times were reviewed using conventional sources and photovoltaic energy. The air conditioning system was found to be outdated and needs to be replaced with a leaner, more efficient one. However, portable electric generators should not be disabled, since they will serve as a backup on days when sunshine is the minimum necessary to recharge the batteries, with a contribution of close to 13.5% of the energy. These findings are useful for systems that are part of the jacket dipping process (rehabilitation of trenchless drainage pipes) used by municipal companies that provide home services.